Time to Loading Dose and Risk of Recurrent Events in the SOCRATES Trial. Issue 3 (March 2019) - Molina, Carlos A.; Johnston, S. Claiborne; Ladenvall, Per; Amarenco, Pierre; Albers, Gregory W.; Denison, Hans; Easton, J. Donald; Evans, Scott R.; Held, Peter; Knutsson, Mikael; Minematsu, Kazuo; Röther, Joachim; et al.
Abstract : Background and Purpose—: Recurrent ischemia risk is high in the acute period after cerebral ischemic events. Effects of antiplatelet agents may vary by time to loading dose (TLD). We explored the risk of recurrent events and safety and efficacy of ticagrelor versus aspirin in relation to TLD. Methods—: We randomized 13 199 patients with noncardioembolic, nonsevere ischemic stroke, or high-risk transient ischemic attack to 90-day ticagrelor or aspirin treatment within 24 hours of symptom onset. For this analysis, 13 126 patients were categorized by TLD as <12 hours or ≥12 hours from start of index event. The primary end point was the composite of stroke, myocardial infarction, or death within 90 days. Major bleeding was the primary safety end point. Results—: TLD was <12 hours in 4403 (33.5%) and ≥12 hours in 8723 (66.5%). The Kaplan-Meier% for the primary end point for all patients with TLD<12 hours was 7.5% versus 6.9% in TLD≥12 hours. Among patients with TLD<12 hours, the primary end point occurred in 147/2196 (6.8%) randomized to ticagrelor and in 184/2207 (8.3%) randomized to aspirin (hazard ratio, 0.79; 95% CI, 0.64–0.98; P =0.036). Among patients with TLD≥12 hours, the primary end point occurred in 6.7% patients randomized to ticagrelor versus 7.0% to aspirin (hazard ratio, 0.95; 95% CI, 0.81–1.12; P =0.55). There was no significant treatment-by-TLD interaction. Major bleeding rates were comparable on ticagrelor and aspirin, regardless of TLD. Conclusions—: The event rate for the primary end point was higher in patients treated early (<12 hours) versus later (≥12 hours). In this exploratory analysis, a larger numerical difference in the primary end point was observed among patients on ticagrelor than on aspirin when TLD was <12 hours compared with ≥12 hours, although the interaction terms for treatment-by-TLD were not significant. For major bleeding, no relation to TLD was observed. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01994720. Abstract : Supplemental Digital Content is available in the text.